Mt. Åreskutan Nunatak: An Arboreal “Roadmap” to the Paleobiogeograpy of the Swedish Scandes and a Possible Pointer Towards a Future Revival of a Richer and More Biodiverse Mountainscape - Kullman, Leif; Öberg, Lisa (European Journal of Applied Sciences, 2024)
In the context of proposed future anthropogenic climate warming, the present study accounts for arboreal responses to recent temperature rise, viewed in the perspective of Lateglacial and early Holocene climate and ecosystem variability. As an analogue to a future warmer world, the focus is on an early deglaciated nunatak in the southern Swedish Scandes, Mt. Åreskutan, with a well-researched arboreal history, embracing periods of climate warming of present-day extent. New research from this and adjacent localities challenges traditional historical narratives, which fail to provide a true picture of deglaciation and vegetation history. It is increasingly evident that common boreal tree species grew close to this summit in a climate, 2-3 °C warmer than at present, during the Lateglacial and early Holocene periods 16 800- 6000 years ago. Based on minimal temperature requirements for tree growth, future warming of the same magnitude would be sufficient for trees to reclaim their lost ground close to this peak. Recent observations of tree saplings and the emergence of genuine “forest plants” at these high elevations, indicate that dispersal mechanisms will not constrain this progressive process. Conceivably, it will not manifest as advancement of a broad forest front. History suggests that pockets of trees, with a ground cover of boreal plant species, will establish in local favourable niches, e. g. sites of vanished glaciers and perennial snow beds. Much of the present-day alpine tundra may be more conservative and resilient to tree invasion, as evident from insignificant upslope movement of forest limits in response to modern climate warming. By and large, continued warming is no imminent threat to alpine biodiversity. An open and diverse high-mountain landscape is likely to prevail.